Fiber Identity Politics and Potential Threats - Muhammad Ridho B. (Indonesian Journal of Multidisciplinary Science, 2022)
The practice of identity politics has again strengthened and dominated the socio-political discourse in this country. Identity politics that appears in all spheres, be it the political stage (elections), social and economic domains, must receive special attention for all stakeholders who still have love for the homeland and patriotism, and require a comprehensive study. This study aims to examine identity politics comprehensively regarding the root causes, forms and patterns of movement and the potential threats it carries. This study uses qualitative research methods, while the data collection techniques are carried out by exploring journals, books, and other information relevant to the study. The results of the study show that identity politics in Indonesia arises due to various factors. The basic causes of identity politics also determine the form and pattern of movements or actions of identity politics that are carried out. In the form of radical action, political reasons, namely ideology, often become the root of the problem which is then closely intertwined with rationalization of action based on identity as the cover. Identity politics is a way to mobilize support and advance the hidden agenda behind the practice of identity politics that is shown. This is of course very vulnerable to the life of the nation and state because such pragmatism will only lead the community to social conflict as a result of the strengthening of identity and self-exclusiveness sentiments or groups and, whether consciously or not, often involve acts of physical or symbolic violence.